It's not all about parents' education, it also matters what they do. Parents' employment and children's school success in Germany - Malte Hoffmann; Christina Boll (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In this paper, we use GSOEP data to explore whether parents employment has an extra effect on the school achievement of their children, beyond the well-established effects of education, income and demography. First, we test whether the source of income or parents unemployment determine children s school achievements. Second, we analyze the effect of job prestige and factors of societal engagement on children s performance. Our results indicate no clear income associations but the existence of an employment channel as well as a social channel from mothers to their kids. A negative role model for girls is found for maternal housework. Moreover, the fathers job prestige is substantial.
Keywords: D13; J62; J22; 330